ANALISIS KEADILAN PROSEDURAL DALAM PENILAIAN KINERJA: PERSPEKTIF SOCIAL EXCHANGE THEORY - Afrianty, Tri Wulida; Putriwahyuni, Silvia (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
Justice in the organizational context is one of the crucial and interesting issues to be discussed. This is because the issue of justice has a great potential to influence employee attitudes and work behavior. Unfortunately, systematic research and publications on organizational justice, especially procedural justice in organizations in Indonesia are still lacking. Therefore, by using the Social Exchange Theory, this study aims to analyze the effect of procedural justice applied to performance appraisals and the mediating role of satisfaction of performance appraisals on the performance of employees of the Direktorat Jenderal Anggaran, Indonesia. Hierarchical regression analysis was applied to test the hypotheses using SPSS software version 25. The results of this study indicate that: 1) procedural justice applied to performance appraisal has a significant effect on employee performance, 2) procedural justice applied to performance appraisal has a significant effect on the satisfaction of performance appraisal, 3) satisfaction of performance appraisal has a significant influence on employee performance, 4) satisfaction of performance appraisal is proven to have a mediating role on the effect of procedural justice that is applied to performance appraisal on employee performance.